spectrophotometric determination of arginine and lysine by alizarin red sulphonate in aqueous solution - Amal Mohammad Saeed; Thabit Saeed Alghabsha (College of Education for Pure Sciences, 2013)
Abstract A simple, rapid and selective spectrophotometric method for the determination of arginine and lysine was developed. The method is based on the proton transfer reaction of arginine and lysine with alizarin red sulphonate in aqueous solution to form a violet coloured product which has maximum absorption at 530 nm. Beer's law obeyed over the range (1-10), (1-11) g.ml-1 for arginine and lysine respectively with a molar absorptivity 7830 l.mol-1.cm-1 for arginine and 5990 l.mol-1.cm-1 for lysine and accuracy (average recovery) 100.63% and precision (RSD) is less than 2.5%. The method has been applied for the determination of arginine in urine.